2003
DOI: 10.1046/j.1600-0749.2003.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Characterization of the Dominant Black Colour Locus in Sheep

Abstract: Dominant black pigment synthesis in sheep is caused by alterations of the melanocortin-1 receptor (MC1-R) coding sequence. Using five bovine microsatellite markers we have mapped the sheep MC1-R gene to chromosome 14, corresponding to the location in other mammalian species. The existence of two independent mutations, both causing an amino acid substitution, in distantly related breeds of sheep, support the hypothesis that the observed black pigment synthesis is caused by a mutual effect of the two mutations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 29 publications
0
39
0
1
Order By: Relevance
“…3). But, more importantly, the clear and statistically significant association between the MC1R variants and plumage color strongly suggests that the Asp119Asn mutation contributes to the expression of the melanic plumage of Santa Ana birds and appears to be dominant, since heterozygous individuals are melanic in plumage (e.g., Kijas et al 1998;Theron et al 2001;Våge et al 2003).…”
Section: Genetics Of Plumage Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…3). But, more importantly, the clear and statistically significant association between the MC1R variants and plumage color strongly suggests that the Asp119Asn mutation contributes to the expression of the melanic plumage of Santa Ana birds and appears to be dominant, since heterozygous individuals are melanic in plumage (e.g., Kijas et al 1998;Theron et al 2001;Våge et al 2003).…”
Section: Genetics Of Plumage Differencesmentioning
confidence: 99%
“…First, breeding experiments indicate that the identical amino acid substitution at the homologous site cosegregates with melanism in several strains of sheep (Våge et al 1999(Våge et al , 2003 and pigs (Kijas et al 1998). Second, amino acid 119 is in the third transmembrane of MC1R and part of a negatively charged pocket that is crucial for binding with the positively charged asparagine residue of its agonist (Lu et al 1998).…”
Section: Genetics Of Plumage Differencesmentioning
confidence: 99%
“…This last is of special interest to breeders since it is impossible to distinguish by eye a sheep with recessive alleles causing black fur colour. This is the reason why black lambs are sometimes born in flocks of white sheep (Våge et al, 2003).…”
Section: The Melanocortin 1 Receptor (Mc1r) Gene and The Agouti Signamentioning
confidence: 99%
“…Våge et al (2003) mapped MC1R to ovine chromosome 14 and identified the two missense mutations, i.e. Met > Lys mutation at position 73 and the Asp > Asn mutation at position 121, which results in a dominant black effect (E D allele) (Våge et al, 1999(Våge et al, , 2003.…”
Section: The Melanocortin 1 Receptor (Mc1r) Gene and The Agouti Signamentioning
confidence: 99%
“…To date, all investigations for genes associated with sheep coat colours have used linkage (for example, Våge et al, 2003;Beraldi et al, 2006) and candidate gene analytic methods (for example, Loehr Norris and Whan, 2008;Gratten et al, 2010). Whereas linkage analysis is a useful tool for identifying rare genetic variants with relatively large phenotypic effects that follow Mendelian laws of inheritance, GWAS is the method of choice for detecting common genetic variants associated with phenotypic variation (for example, Kayser et al, 2008), and a higher resolution can be achieved.…”
Section: Introductionmentioning
confidence: 99%